Building A Quality Ecosystem for Clinical Psychology: Integrating Competence, Ethics, Supervision, and Professional Regulation - Vu Xuan Huong (INTERNATIONAL JOURNAL OF INNOVATIVE RESEARCH IN MULTIDISCIPLINARY EDUCATION, 2026)
An important consideration in clinical psychology is that of professional quality. Having appropriate standards is not enough; they must shape both the training of clinical psychologists and the work that they do. Therefore, all of the elements that contribute to the professional quality of clinical psychologists, that is, competence, ethics, supervision, accreditation and regulation, must function together. This critical integrative review sets out to explore the relationships between these elements. A record-verified PubMed/MEDLINE search was conducted and, where appropriate, citation tracking of identified papers, a targeted search for appropriate, peer-reviewed papers, and the most up-to-date information on the topics of accreditation and regulation in the US and Canada, in Europe/EuroPsy, in the UK, in Australia, in South Africa, and from around the world, from the World Health Organization, was undertaken. The resulting synthesis consists of 35 substantive peer-reviewed papers and 20 normative or regulatory documents from across the globe. Six additional methodological sources informed the review process and critical appraisal. Systematic reviews were assessed using AMSTAR 2 where appropriate, primary studies using design-relevant JBI criteria, and policy and professional documents through an adapted documentary appraisal framework. Several common patterns emerged across otherwise different professional and regulatory systems. Competence was viewed as something that develops over time, depends on context, and must be demonstrated in practice. Ethics was not simply a body of rules but a professional capacity expressed through judgment and action. Supervision served both to support development and to evaluate readiness for practice, including its gatekeeping responsibilities, while regulation provided an ongoing structure for protecting the public beyond the point of initial entry into the profession. Drawing these strands together, the review introduces the Competence-Ethics-Supervision-Regulation (CESR) Quality Ecosystem and identifies four mechanisms through which its components are connected: alignment, observability, feedback, and proportionality. Four testable propositions are proposed to support further empirical inquiry. Overall, the findings suggest that quality depends less on adding requirements than on making the main parts of the professional system work together. Strong links among education, supervision, assessment, regulation, professional learning, and service-user experience are more likely to support safe, effective, culturally responsive, and trustworthy care.